Perancangan Interior Galeri Batik Mangrove di Surabaya - Raphael G M Halim (Intra, 2013)
Mangrove jungle is one of the new domestic place in Surabaya. Now, many contractor is making a new properties in there & they destroyed it. Actually, mangrove jungle can help many person to get a many money. Lulut Sri Yuliani is a leader made any product original from the jungle. She know the function of the junggle and She make a batik mangrove, “sirup mangrove”, accessories for woman and man. She made batik with different process of the others. Lulut produce batik on the little garage of her house with a few people.. In the other hand, the purpose of the project is give information for many people that mangrove jungle is important for Surabaya and please stop destroy it. The main problem on this desain is how to design interior gallery to inform about batik, and many product of mangrove and the design can be unity with the display, and interior a workshop to teach how to make a batik for research to inform and educate about mangrove jungle and the last interior galeri used modern natural theme with mangrove jungle characteristic and also batik mangrove character. This research used deskriptif method research. This concept is expresion of bogem which inspired by bogem trees and aplied for shape, color and material on ceiling, wall, floor, ornament and display cabinet. The design style is modern with natural theme.